Optimal Design of NRD Grating Bandpass Filters for THz Application Using GA and EIM - Md. Iquebal Hossain Patwary; Akito Iguchi; Yasuhide Tsuji (IEEE Photonics Journal)
Compact and low-loss waveguide devices are highly desired in the development of THz-wave circuits. Nonradiative dielectric (NRD) waveguides having simple structures and very low loss are promising platforms for THz-wave circuits, and previously some basic devices have been reported. As the NRD guide has a non-radiative nature, the NRD grating bandpass filters that have been reported for millimeter-wave circuits are more suitable to design in THz-wave range. In this paper, we present THz NRD grating bandpass filters and develop an efficient optimal design method to realize these devices based on genetic algorithm (GA) and effective index method (EIM). The optimized device achieved the desired flat top transmission band within the aimed frequency range with only 0.46 dB of avg. IL in the passband, where the reflection in the passband is better than −20 dB. The results obtained with EIM are also verified by three-dimensional finite element method (3D-FEM). The fabrication tolerance of the proposed devices has also been discussed in detail.